2021
DOI: 10.3390/s21082678
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Memory in a Spiking Neural Network with Robot Embodiment

Abstract: Cognitive maps and spatial memory are fundamental paradigms of brain functioning. Here, we present a spiking neural network (SNN) capable of generating an internal representation of the external environment and implementing spatial memory. The SNN initially has a non-specific architecture, which is then shaped by Hebbian-type synaptic plasticity. The network receives stimuli at specific loci, while the memory retrieval operates as a functional SNN response in the form of population bursts. The SNN function is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Figure 1A shows an example of the network reorganization provoked by a stimulus. Recently, it has been shown that there is an interplay between the anatomic architecture and functionality, and functional changes can drive the rebuilding of the network and vice versa ( Lobov et al, 2021b ).…”
Section: Spiking Neural Network As An Alternative For Building Reflec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1A shows an example of the network reorganization provoked by a stimulus. Recently, it has been shown that there is an interplay between the anatomic architecture and functionality, and functional changes can drive the rebuilding of the network and vice versa ( Lobov et al, 2021b ).…”
Section: Spiking Neural Network As An Alternative For Building Reflec...mentioning
confidence: 99%
“…Spatial computing in small neural circuits and modular SNNs can simulate Pavlovian conditioning and operant learning in neurorobots ( Lobov et al, 2020b , 2021a ). Another possible way to implement spatial computations is cognitive maps and spatial memory with positive ( Ponulak and Hopfield, 2013 ) or negative ( Lobov et al, 2021b ) environmental stimuli ( Figure 1C ). Note that due to the presence of spontaneous activity in SNNs (unlike ANNs), they can “live” without external input, determining the “behavior” of neurorobots ( Lobov et al, 2020b , 2021a , 2021b ).…”
Section: Spiking Neural Network As An Alternative For Building Reflec...mentioning
confidence: 99%
“…One application is a model of spatial memory implemented in an SNN that was used on a robot moving in an environment with neutral and harmful regions. In that application, STDP rearranges the couplings in the SNN and forms spatial memory similar to cognitive maps associated with the negative experience that resulted in a learning robot to avoid harmful zones [ 14 ]. Another area of cognitive development is the application of SNN for associative learning of perceptual information.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, there should be a gap between molecular and cellular levels of implementation and its functionality at the cognitive level. Scholars proposed a variety of conceptual, mathematical, and computational models of neuronal networks pretending to implement cognitive functions, such as learning and memory [3][4][5][6][7][8][9]. Systems neuroscience views memory as a substantially complicated paradigm involving different types and forms.…”
Section: Introductionmentioning
confidence: 99%